Development and validation of a high throughput UPLC-MS/MS method for simultaneous quantification of esomeprazole, rabeprazole and levosulpiride in human plasma - Raja Haranadha Babu Chunduri; Gowri Sankar Dannana (Elsevier, 2016)
A high throughput ultra pressure liquid chromatography-mass spectrometry (UPLC-MS/MS) method with good sensitivity and selectivity has been developed and validated for simultaneous quantification of esomeprazole, rabeprazole and levosulpiride in human plasma using lansoprazole as internal standard (IS). The extraction method based on liquid-liquid extraction technique was used to extract the analytes and IS from of 50 µL of human plasma using methyl tert-butyl ether:ethyl acetate (80:20, v/v), which offers a high recovery. Chromatographic separation of analytes and IS was achieved on a Hypersil gold C18 column using gradient mobile phase consisting of 2 mM ammonium formate/acetonitrile. The flow rate was set at 0.5 mL/min to elute all the analytes and IS within 1.00 min runtime. Detection of target compounds was performed on a triple quadruple mass spectrometer by multiple reaction monitoring (MRM) mode via positive electrospray ionization (ESI). Method validation results demonstrated that the developed method has good precision and accuracy over the concentration ranges of 0.1-2000 ng/mL for each analyte. Stability of compounds was established in a battery of stability studies, i.e., bench top, autosampler, dry extract and long-term storage stability as well as freeze-thaw cycles. The validated method has been successfully applied to analyze human plasma samples for application in pharmacokinetic studies.